2015
DOI: 10.1039/c5ra21176j
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid TiO2–acetylacetonate amorphous gel-derived material with stably adsorbed superoxide radical active in oxidative degradation of organic pollutants

Abstract: ˙O2−superoxide radicals are firmly adsorbed on the surface of the hybrid material giving oxidative degradation without any light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 38 publications
6
63
0
4
Order By: Relevance
“…TiO 2 is frequently produced as bulk or nanoparticles from physical gels, 24,25 while to attain chemical gels the stabilization of the sol against the uncontrolled hydrolysis of titanium alkoxides is required. It can be achieved using complexing agents of Ti 4+ , such as b-diketones, including acetylacetone (Hacac), 23,26,27 forming heteroleptic alkoxide complexes able to give micelles by self-assembly. 28 Chemical gels obtained in this way ensure a high homogeneity of the oxide structure and provide porous xerogels with macroscopic granulometry and specic features related to the organic complexing agent used.…”
Section: Synthesis Of Gel-derived Defective Tio 2 Materialsmentioning
confidence: 99%
“…TiO 2 is frequently produced as bulk or nanoparticles from physical gels, 24,25 while to attain chemical gels the stabilization of the sol against the uncontrolled hydrolysis of titanium alkoxides is required. It can be achieved using complexing agents of Ti 4+ , such as b-diketones, including acetylacetone (Hacac), 23,26,27 forming heteroleptic alkoxide complexes able to give micelles by self-assembly. 28 Chemical gels obtained in this way ensure a high homogeneity of the oxide structure and provide porous xerogels with macroscopic granulometry and specic features related to the organic complexing agent used.…”
Section: Synthesis Of Gel-derived Defective Tio 2 Materialsmentioning
confidence: 99%
“…The final hybrid TiO 2 -melanin nanostructures have shown excellent antimicrobial activity even without irradiation, owing to their ability in generating reactive oxygen species (ROS) [140][141][142][143]. Another interesting family of compounds, yet still poorly studied in the frame of CT complexes, are β-diketones: acetylacetone (2,4-pentanedione) has been shown to considerably shift the absorption onset of TiO 2 [101,144] and ZrO 2 [145] through LMCT. Moreover, hybrid oxide-acetylacetonate materials prepared by a sol-gel procedure exhibit the peculiar ability to generate and stabilize on their surface the superoxide radical anion (a pivotal ROS), with a consequent activity in organic pollutants degradation even in the dark [144][145][146][147].…”
Section: Lmct-sensitized Tiomentioning
confidence: 99%
“…Another interesting family of compounds, yet still poorly studied in the frame of CT complexes, are β-diketones: acetylacetone (2,4-pentanedione) has been shown to considerably shift the absorption onset of TiO 2 [101,144] and ZrO 2 [145] through LMCT. Moreover, hybrid oxide-acetylacetonate materials prepared by a sol-gel procedure exhibit the peculiar ability to generate and stabilize on their surface the superoxide radical anion (a pivotal ROS), with a consequent activity in organic pollutants degradation even in the dark [144][145][146][147]. In most reports, sensitized hybrid materials are prepared by surface adsorption on commercial or synthesized TiO 2 nanoparticles, whereas LMCT sensitized thin films have been seldom investigated, besides some TiO 2 coatings whose surface was functionalized with catechol [126,148].…”
Section: Lmct-sensitized Tiomentioning
confidence: 99%
See 1 more Smart Citation
“…In order to solve this problem, scientists have conducted lots of meaningful and in-depth research. For instance, Aronne et al found that high Ti 3+ self-doping TiO 2−x not only has a wide range of visible light responses, but also has a low recombination rate of electron-hole pairs [17]; Sannino et al fabricated hybrid TiO 2 -acetylacetonate amorphous gel-derived material with stably adsorbed superoxide radical (O 2 •− ) active in oxidative degradation of organic pollutants in the absence of any light irradiation [18,19]. It has been reported that using the strong oxidant of persulfate ion (S 2 O 8 2− ) (with redox potential of 2.05 V) is effective for degrading organic pollutions in water solution through direct chemical oxidation [20].…”
Section: Introductionmentioning
confidence: 99%